A basic and effective liquid phase microextraction with a novel automated mixing system for the determination of cobalt in quince samples by flame atomic absorption spectrometry. (1st November 2021) - Gösterişli, Tuğçe Unutkan; Zaman, Buse Tuğba; Bakirdere, Emine Gülhan; Keyf, Seyfullah; Bakırdere, Sezgin
Highlights: A sensitive SCTS-PLPME -SQT-FAAS method was developed for cobalt determination. High percent recoveries were obtained in quince samples. 33.7 times enhancement in detection power was achieved compared to conventional FAAS. The method provides environmental friendly, easy, cheap and fast measurements. Abstract: A new, green, and simple liquid-phase microextraction method namely sieve conducted two syringe-based pressurized liquid-phase microextraction methods was combined with flame atomic absorption spectrometry for the preconcentration and determination of cobalt. For this aim, a novel automated syringe mixing system was developed to be used in the developed extraction procedure. Two syringes were connected to each other by an apparatus having six holes to produce efficient dispersion of the extractant. The pressure created between the two syringes by the forward and backward movements of the syringe plungers created an efficient dispersion of the extractant. In the present study, ligand as complexing agent was synthesized in our laboratory. Limits of detection and quantification were determined to be 1.8 and 6.0 μg L -1, respectively. A 33.7-fold enhancement in detection power was obtained with the developed method. Method was effectively applied for the determination of cobalt in quince samples.